2020
DOI: 10.15381/rinvp.v23i2.19228
|View full text |Cite
|
Sign up to set email alerts
|

Violencia de género y riesgo de feminicidio en alumnas de universidades públicas y privadas de Lima Metropolitana

Abstract: El objetivo del estudio es evaluar la relación entre las actitudes hacia la violencia de género y el extremo riesgo de la pareja de ser víctima de violencia o feminicidio, con estudiantes de género femenino en universidades públicas y privadas de Lima Metropolitana, siendo los instrumentos a utilizar la Escala de Actitud Hacia la Violencia de Género y la Escala de Evaluación del Riesgo. La aplicación de los instrumentos se efectúa sobre una muestra de estudiantes de universidades públicas y privadas de las áre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
0
0
2
Order By: Relevance
“…It is not a cause-effect explanation but a correlational expression in which the two variables move in parallel in the same direction: more, more and less, less. This is consistent with the study by Velásquez et al (44) on gender violence and risk of femicide (in female students from public and private universities in Metropolitan Lima), in which it was evident that the greater the attitude of rejection of violence, the less experimentation of violence existed and that women from private universities with less rejection of gender violence experienced more physical, sexual and economic violence. The same occurs in two other studies carried out in the eld of higher education (45,46) in which it is shown that attitudes of acceptance towards gender violence are directly associated with discriminatory behaviour's based on sex.…”
Section: Discussionsupporting
confidence: 92%
“…It is not a cause-effect explanation but a correlational expression in which the two variables move in parallel in the same direction: more, more and less, less. This is consistent with the study by Velásquez et al (44) on gender violence and risk of femicide (in female students from public and private universities in Metropolitan Lima), in which it was evident that the greater the attitude of rejection of violence, the less experimentation of violence existed and that women from private universities with less rejection of gender violence experienced more physical, sexual and economic violence. The same occurs in two other studies carried out in the eld of higher education (45,46) in which it is shown that attitudes of acceptance towards gender violence are directly associated with discriminatory behaviour's based on sex.…”
Section: Discussionsupporting
confidence: 92%
“…No obstante, la violencia sexual y psicológica incrementa entre personas con estudios superiores (Garcés et al, 2020). Esto contrasta con los hallazgos de Velásquez et al (2020), quienes señalan que por lo general son las estudiantes jóvenes quienes muestran mayor rechazo a actitudes machistas y violencia de género y, a su vez, entre quienes menos prevalece. Los resultados de algunos estudios muestran que la totalidad de alumnas entrevistadas han sufrido de acoso sexual en al menos una ocasión durante su vida (manifiesto en forma de piropos, miradas obscenas, persecución, tocamientos o exhibicionismo), y es precisamente en los espacios universitarios donde señalan encontrarse en mayor riesgo (Chan, 2021;Martínez y Salazar, 2022).…”
Section: Discussionunclassified
“…Siguiendo a la ONU, entendemos por violencia de género cualquier forma de violencia derivada de la condición de ser mujer que resulte en daño físico, sexual o psicológico, abarcando amenazas, coerción o privación injusta de la libertad. Velásquez et al (2020) recogen la denominación "violencia-castigo" aplicada al contexto de relaciones de pareja heterosexuales con dinámicas patriarcales, donde esta violencia puede incluir prácticas extremas como esclavización, violación y asesinato. Esto es relevante porque el interior de una relación de pareja resulta un lugar común para las situaciones de violencia de género.…”
Section: Desarrollo Necesidad Del Feminicidio Como Tipo Penalunclassified